6x+6(-3)=-8

Simple and best practice solution for 6x+6(-3)=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+6(-3)=-8 equation:


Simplifying
6x + 6(-3) = -8

Multiply 6 * -3
6x + -18 = -8

Reorder the terms:
-18 + 6x = -8

Solving
-18 + 6x = -8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 6x = -8 + 18

Combine like terms: -18 + 18 = 0
0 + 6x = -8 + 18
6x = -8 + 18

Combine like terms: -8 + 18 = 10
6x = 10

Divide each side by '6'.
x = 1.666666667

Simplifying
x = 1.666666667

See similar equations:

| 10q-9q=4 | | -j=-103 | | 2(3x+4)+x= | | 2-c=3 | | [-5x]=10 | | 9(2y+5)-2y-8= | | 5x^3-32x^2-21x=0 | | 8.8=x+x | | x-(-16)=-3 | | (2-w)(4w-3)=0 | | 14c-9c+5=15 | | 2(-7-8n)+(8-3n)=79 | | 6.3x-5+x-2.1= | | 8n-12+14=12n-4+4n+2 | | 5x(2x-3)=15 | | 51x^333(-16+9x^2)=0 | | 10x^2+46x=-24 | | 3n-2=1/2 | | 13a-12a=16 | | 4(a+3)-3a=3 | | 12x^3-12x^2+3x= | | 4z+6.2+3.8z+2.1z-1= | | 12z=.8z | | 8x-5=4x-2x | | 4y=2(x-3) | | 14-6a+7a=-5-2 | | 1a-3=1 | | 25x^2+25x-150=0 | | 0.91=312/x | | -121=-7x-6x+9 | | -9r-4r=13 | | -8(-2-4a)=-208 |

Equations solver categories